Exploring the Relationship Between Work Life Quality and Professional Ethics Among Dentists (Acta Scientiarum. Health Sciences, 2025)
This study aimed to assess the relationship between Work Life Quality and Professional Ethics Among Dentists. A single-phase survey study involving 68 dentists was carried out. Data was collected using Work Life Quality, and Gregory's Work Ethics Questionnaires. The data was analyzed using descriptive analysis, unpaired t-test, Analysis of Variance,Pearson correlation coefficient, and a Simple Linear Regression Analysis. Our findings indicated that 51.5% of participants (n = 35) reported a high level of work-related quality of life and 88.2% of participants have a high work ethic. Significant differences were observed between the work quality of life and type of organizational activity (p = 0.019). Dentists in private practice reported the highest mean score (68.21), while those in public positions had the lowest (53.19). A significant positive correlation was between work quality of life and work ethic (r = 0.35, p = 0.003). The study found that a substantial proportion of dentists reported high work quality of life, which was positively correlated with their adherence to work ethics. These findings suggest that improving work ethics can enhance the quality of life for dentists in both professional and personal contexts.